A brief review of membrane vesicles from Streptococcus mutans - Qiu, Lili; Chen, Qinxia; Zheng, Gaozhe; Dong, Haiyun; Xu, Muxin; Zhou, Jieyu; Zhang, Lingjun; Sun, Yan; Wang, Min; Pan, Yangyang; Yu, Jie; Pan, Yihuai; et al. (Frontiers in Microbiology, 2025)
Streptococcus mutans (S. mutans), a prime conditionally cariogenic organism, produces membrane vesicles (MVs) containing proteins, nucleic acids, and lipids, including cariogenic virulence factors. Factors including culture conditions, peptide signals, bacterial strains, and genes affect the size and contents of MVs. Based on the composition of their contents, MVs play a wide range of roles in self-regulation, microbial interspecies communication, and microbe–host interactions, which have important potential applications in the fields of vaccine research and disease treatment. In this study, we summarize recent developments in the biogenesis, influencing factors, composition, and functions of S. mutans MVs to lay a theoretical foundation for their potential clinical application and future research.